Determining and monitoring of project contingency sum for building developments in Ghana. (A case Study in Ashanti and Greater Accra Regions) - Oduro Asamoah, Richard (2011)
A project report presented in partial fulfillment of the requirements for a degree of Master of Science in Construction Management.